Nanoencapsulation of antioxidant peptides from Lupinus mutabilis in chitosan nanoparticles obtained by ionic gelling and spray freeze drying intended for colonic delivery. (December 2022) - Intiquilla, Arturo; Jiménez-Aliaga, Karim; Iris Zavaleta, Amparo; Gamboa, Alexander; Caro, Nelson; Diaz, Mario; Gotteland, Martin; Abugoch, Lilian; Tapia, Cristian
Abstract: Oxidative stress has long been associated with the pathogenesis of inflammatory bowel disease (IBD), and it has been suggested that the combined administration of antioxidants and anti-inflammatory agents may be helpful for its treatment. Biopeptides from plant proteins, such as soybean glycinin tripeptide VPY, effectively inhibit pro-inflammatory mediators in intestinal epithelial and immune cells, which are both involved in the pathogenesis of IBD. This study aimed to produce antioxidant biopeptides from proteins of Lupinus mutabilis seeds and then encapsulate them in chitosan nanoparticles (NPs) for colonic delivery. An antioxidant peptide fraction of less than three kDa (UF3) was obtained and added at different concentrations (0.1–0.4 mg/ml) in chitosan solutions. The NPs were prepared by gelation with tripolyphosphate (CTPP-UF3) or spray freeze-drying of the chitosan solution (SFDC-UF3). Sizes of 332 ± 13 and 465 ± 58 nm and maximum encapsulation efficiencies of 63.80 and 71.75%, respectively, were obtained. UF3 maintained its antioxidant capacity (>80%) and showed different release profiles in 1X PBS buffer at pH 7.4, depending on the encapsulation method. FT-IR showed hydrogen bonding and electrostatic interactions between the peptide and chitosan. Both nanosystems maintained cell viability greater than 70% in colonic cell lines HT-29. These results show that both methods are appropriate for the nanoencapsulation of UF3 and can be used to design nanoparticles for colonic delivery. Highlights: An antioxidant peptide fraction (<3 kDa) was obtained from Lupinus mutabilis seeds. CTPP and SFDC chitosan nanoparticles loaded with UF3 were prepared. FT-IR spectroscopy revealed hydrogen bonding and electrostatic interaction between UF3 and chitosan. CTPP and SFDC show controlled release of UF3 and retain antioxidant capacity. Chitosan NPs were not cytotoxic in the HT-29 cell line by the MTT assay.